Fluid Dynamic Analysis and Residence Time Distribution Determination for Rectangular Based Spouted Beds - Reyes-Salinas, A; Henriquez-Vargas, L; Bubnovich, V; Castro-Valenzuela, P; Castro-Valenzuela, P; Pailahueque-Barahona, N (Elsevier B.V., 2021)
Fluid dynamic characterization for a set of three serial rectangular based spouted beds (RBSB) using sawdust or turnip seeds, were made. In batch experiences, the minimum spouting velocity (Ums) and the maximum pressure drop (ΔPmax) were determined based on the bed height and moisture content. With respect to the continuous solid feed experiences, initially the conditions that allowed the stationary operation for 1, 2 and 3 beds connected in series, were determined. Following, injecting colored particles and with an image analysis it was possible to determine the residence time distribution (RTD). When compared with expressions from literature, good agreement was found for Ums, whereas for ΔPmax an expression is proposed that includes the sphericity of the particles. The RTDs were adjusted with the tank in series model, finding that the effects of solids feed rate, air flow and moisture content are significant for each solid RTD. © 2020 Elsevier B.V.